2014
DOI: 10.1007/s13201-014-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of osmotic backwash induced by sodium chloride salt solution in controlling SWRO membrane fouling

Abstract: A study was conducted to evaluate the efficacy of osmotic backwash induced by high salt (NaCl) concentration solution on feed side of seawater reverse osmosis (SWRO) membranes, online and offline, in controlling membrane fouling and therefore minimizing/ eliminating the need for chemical cleaning. SWRO membranes were deliberately fouled by feeding seawater from an open intake located on the Arabian Gulf Coast without dosing chemicals. The fouled membranes were subjected to offline cleaning with the salt soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Despite its potential, widespread adoption of OIC in practice has been challenged by operational challenges. A study by Farooque et al [17], for example, found OIC to be ineffective at mitigating fouling in commercial spiral-wound modules used for seawater desalination. Furthermore, recent experiments by Labban et al [11] using organic foulants demonstrate the mechanism underlying OIC and visually capture the foulant layer detachment and cleaning procedure as they occur in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential, widespread adoption of OIC in practice has been challenged by operational challenges. A study by Farooque et al [17], for example, found OIC to be ineffective at mitigating fouling in commercial spiral-wound modules used for seawater desalination. Furthermore, recent experiments by Labban et al [11] using organic foulants demonstrate the mechanism underlying OIC and visually capture the foulant layer detachment and cleaning procedure as they occur in situ.…”
Section: Introductionmentioning
confidence: 99%